The Values of Sufism As Foundation of Tolerance and Brotherhood in Multicultural Society - Abubakar, Abubakar (International Journal on Advanced Science, Education, and Religion, 2025)
This article examines the values ​​of Sufism as the foundation of tolerance and brotherhood in a multicultural society. Sufism, or Sufism, is a spiritual dimension of Islam that emphasizes the purification of the soul through love, humility, and simplicity. In the context of a diverse society, Sufism promotes the values ​​of universal love, sincerity, and ihsan as an important basis for building tolerance and social cohesion. These values ​​form a dialogical attitude that respects differences as common wealth, in accordance with the principle of multiculturalism that prioritizes diversity. This study aims to identify and analyze the role of Sufism values ​​in building social harmony in a pluralistic society. The research method used is a library approach, through the analysis of various written sources, such as books and scientific journals, to understand the concept of Sufism values ​​and their application in a social context. The results of the analysis show that Sufism not only functions as an individual spiritual practice, but also as an effective social tool to promote peace, universal brotherhood, and acceptance of diversity. In conclusion, Sufism makes a significant contribution in strengthening tolerance and appreciation for cultural diversity, creating sustainable harmony within society.